ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL STATEMENT FRAUD DALAM PERSPEKTIF FRAUD PENTAGON - Ade Rizky Novitasari; Anis Chariri (Diponegoro Journal of Accounting, 2018)
This study aims to obtain empirical evidence and to examine the elements of fraud in fraud pentagon theory against indications of financial statement fraud on nonfinancial sector companies in Indonesia at 2009-2014. Independent variables in this research were financial stability, financial target, external pressure, nature of industry, ineffective monitoring, change in auditor, change of director, and frequent number of CEO’s picture, while the dependent variable was financial statement fraud.The population in this study was nonfinancial companies listed on the Indonesia Stock Exchange in 2008 to 2013, based on the investigation result of Indonesia Financial Services Authority in 2009 to 2014 towards the listed companies that proved have done the VIII.G.7 infraction, the financial statement fraud. Total samples used in this study were 60 companies, consist of 30 companies which classified had done the financial statement fraud, and 30 companies which not classified had done the fraud as matched companies by the criteria on the same of industry and total asset. This research was conducted by quantitative methods using secondary data. Data analysis was performed by the descriptive statistic analysis, multikolonieritas test, and hypothesis test with logistic regression analysis.The results of this study indicate that there are two variables which were significant positive in influencing the financial statement fraud, including and the change in auditor and frequent number of CEO's picture. These variables represent the two elements in a pentagon fraud Crowe's theory; rationalization and arrogance.